Relation among Stakeholders in HIV/AIDS Response Case Study: Palu Municipality - Mustika Sari; Gabriel Lele (Policy & Governance Review, 2017)
This study aims at acquiring data and information regarding why there is an increasing annual trend of HIV/AIDS in the city of Palu. In order to answer the aforementioned question, this research focused on the relation established among stakeholders involved in HIV/AIDS response.The ongoing trend of HIV/AIDS in the city of Palu has always been confronted with HIV/AIDS response policies in the form of: (1) fnding as much cases as possible; (2) preventive measures; (3) policies on medication, support and treatment/care; and (4) empowerment policy. However,research results show that the increasing trend of HIV/AIDS found in the Palu Municipality is due to the poorly established relation among stakeholders, be it key stakeholders, primary stakeholders, or secondary stakeholders. In addition to the poor relationship established among stakeholders being observable through a number of negative characteristics seen in their interactional and relational paterns, it was also found that the said relation was inﬂuenced by each of the stakeholders’ power and interests.